Human rights and ASEAN Indonesian and international perspectives - Tan, Kevin; Cohen, David (David J.); Nabahan, Aviva (World Scientific, 2021)
"Human Rights in ASEAN: Indonesian and International Perspectives is a collection of 13 essays that not only offers fresh new insights on the different facets of human rights and their protection in ASEAN, but also 'insider' accounts of the development of the ASEAN Inter-Governmental Commission for Human Rights. These valuable perspectives have never been shared publicly, and offer a view from both the state and non-governmental organisations' (NGO) perspectives. In addition to these valuable perspectives, this book offers a number of significant case studies of how human rights has been implemented, and the challenges it faces in ASEAN in general, and in Indonesia particularly"-- Provided by publisher.